Fluoride and Casein Phosphopeptide-Amorphous Calcium Phosphate - Reynolds, E.C.; Cai, F.; Cochrane, N.J.; Shen, P.; Walker, G.D.; Morgan, M.V.; Reynolds, C. (Journal of dental research, 2008)
Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) slows the progression of caries and remineralizes enamel subsurface lesions. The aim of this study was to determine the ability of CPP-ACP to increase the incorporation of fluoride into plaque and to promote enamel remineralization in situ. Randomized, double-blind, cross-over studies involved mouthrinses and dentifrices containing CPP-ACP and fluoride. The mouthrinses were used for 60 sec, three times/day for 5 days, and supragingival plaque was collected and analyzed for F. The dentifrices were rinsed as a water slurry for 60 sec four times/day for 14 days in an in situ model. The addition of 2% CPP-ACP to the 450-ppm-F mouthrinse significantly increased the incorporation of fluoride into plaque. The dentifrice containing 2% CPP-ACP produced a level of remineralization similar to that achieved with a dentifrice containing 2800 ppm F. The dentifrice containing 2% CPP-ACP plus 1100 ppm F was superior to all other formulations.